Flexible stretchable nano-silver aerogel conductive paste and preparation method thereof
Patent Information
- Application Number
- CN202510543473.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-28
- Publication Date
- 2026-10-30
AI Technical Summary
该方法的缺点是:导电网络易因拉伸或形变发生不可逆断裂,缺乏动态自修复能力,导致电阻稳定性差,机械混合或溶液共混法难以实现导电填料的均匀分散,影响导电性能
[0050]本发明实施例的柔性可拉伸纳米银气凝胶导电浆料的制备方法,以高分子支架作为柔性基底,提供支撑和形变能力,通过硫醇封端剂将纳米银颗粒精准定位在高分子链端点,使得材料拉伸时颗粒间距可控变化,维持导电通路。且硫醇封端剂与高分子反应,使得高分子链间二硫键(S-S)与银-硫(Ag-S)配位键协同,可以实现材料的拉伸自修复。
Smart Images

Figure CN123017598A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive paste technology, and in particular to a flexible and stretchable nano-silver aerogel conductive paste and its preparation method. Background Technology
[0002] Flexible and stretchable conductive materials are a new type of material that combines conductivity and mechanical flexibility. They can maintain stable electrical properties under deformation conditions such as stretching, bending, and torsion, and have broad application prospects in wearable electronic devices, soft robots, biomedical sensors, and other fields.
[0003] Currently, there are three main technical routes for the preparation of flexible and stretchable conductive materials:
[0004] One method involves using silver nanowires, carbon nanotubes, or graphene as conductive fillers, which are then combined with elastomers (such as polydimethylsiloxane or polyurethane) and prepared via mechanical mixing or solution blending. The drawbacks of this method are that the conductive network is prone to irreversible breakage due to stretching or deformation, lacks dynamic self-healing capabilities, resulting in poor electrical resistance stability. Furthermore, mechanical mixing or solution blending methods struggle to achieve uniform dispersion of the conductive filler, affecting conductivity.
[0005] Secondly, pre-stretching or patterning designs are used to introduce microcrack structures into the material to improve tensile properties. The disadvantages of this method are: microcracks are irreversible after propagation, conductive pathways cannot self-repair after breakage, and resistance increases significantly with microcrack propagation. Furthermore, this method is complex, and pre-stretching and patterning designs increase the difficulty and cost of fabrication.
[0006] Third, elastic networks can be constructed through chemical or physical cross-linking to enhance the mechanical properties and electrical conductivity of materials. The drawbacks of this method are: the cross-linked structure limits the dynamic recombination ability of molecular chains, it is difficult to repair damaged conductive pathways in situ, and the electrical stability depends on the integrity of the initial network. Summary of the Invention
[0007] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention proposes a flexible and stretchable nano-silver aerogel conductive slurry and its preparation method, which can achieve reversible fracture / reconstruction of conductive materials and ensure the stability of conductive pathways.
[0008] To solve the above-mentioned technical problems, the technical solution provided by the present invention is as follows:
[0009] The method for preparing a flexible and stretchable nano-silver aerogel conductive paste according to a first aspect of the present invention includes the following steps:
[0010] S1, prepare a thiol-terminated prepolymer solution;
[0011] S2, add silver ion solution and reducing agent to the thiol-terminated prepolymer solution to reduce and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints, wherein the TEM number-average particle size of the silver nanoparticles is 5-20 nm and the particle size distribution index is 0-0.3.
[0012] S3, add a crosslinking agent to the colloidal solution and freeze it in a directional manner to form a gel, then immerse the gel in a displacement agent to displace it, thus obtaining a nano-silver aerogel;
[0013] S4, the nano-silver aerogel is pulverized and uniformly mixed with silicone oil to obtain the flexible and stretchable nano-silver aerogel conductive slurry.
[0014] Preferably, step S1 includes:
[0015] A polymeric prepolymer and a thiol-terminated agent are added to a solution and stirred until homogeneous to obtain the thiol-terminated prepolymer solution.
[0016] The molar ratio of the polymer prepolymer to the thiol end-capping agent is 1:(0.1-5).
[0017] During the stirring process, the ambient temperature is 40℃~80℃, the stirring speed is 200r / min~500r / min, and the stirring time is 1.5h~3h.
[0018] Preferably, in step S1,
[0019] The polymer prepolymer is selected from one of polyurethane, polydimethylsiloxane, or polyacrylic acid.
[0020] The thiol end-capping agent is selected from one of 1,4-butanedithiol, 1,6-hexanedithiol, dithiodipropionic acid, mercaptopolyethylene glycol, 3-mercaptopropyltrimethoxysilane, cysteine, pentaerythritol tetramethylolpropane, 1-octylthiol, mercaptoacetic acid, or mercaptoethanol.
[0021] The solution is selected from one of tetrahydrofuran, toluene, N,N-dimethylformamide, acetone, N-methylpyrrolidone, propylene glycol methyl ether acetate, or supercritical carbon dioxide.
[0022] Preferably, step S2 includes:
[0023] A silver ion solution and a reducing agent are added to the thiol-terminated prepolymer solution, and the mixture is ultrasonically dispersed at an ultrasonic frequency of 20 kHz to 60 kHz for 15 min to 60 min. Then, the mixture is reacted at an ambient temperature of 40 ℃ to 80 ℃ for 0.5 h to 3 h to reduce and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints.
[0024] Preferably, in step S2,
[0025] The molar ratio of silver ions to reducing agent in the silver ion solution is 1:(1-8).
[0026] Preferably, in step S2,
[0027] The silver ion solution is selected from one of silver nitrate, silver acetate, silver fluoroborate or silver lactate, and the concentration of silver ions in the silver ion solution is 0.01 mol / L to 0.2 mol / L.
[0028] Preferably, in step S2,
[0029] The reducing agent is selected from one of ascorbic acid, sodium borohydride, sodium citrate, or glucose.
[0030] Preferably, step S3 includes:
[0031] A crosslinking agent is added to the colloidal solution, which is then injected into a mold and placed in an environment of -50℃ to -10℃ for 3 to 10 hours to induce ice crystal growth and form oriented channels with a hierarchical porous structure, thus forming a gel.
[0032] The oriented channels include primary channels and secondary channels. The primary channels are formed by ice crystals growing along a temperature gradient, with a pore size of 10-50 μm and an aspect ratio greater than 5. The secondary channels are formed by the aggregation of the silver nanoparticles in the gaps between the ice crystals, with a pore size of 100-500 nm. The volume ratio of the primary channels to the secondary channels is 1:(0.5-2).
[0033] The gel was immersed in a displacement agent to displace water, and then dried in a supercritical CO2 environment to obtain the nano-silver aerogel.
[0034] The volume ratio of the gel to the displacement agent is 1:(3-10), and the displacement time is 2h-24h.
[0035] The drying environment is characterized by a temperature of 32℃ to 50℃, an air pressure of 7.5 MPa to 20 MPa, and a duration of 6 hours to 24 hours.
[0036] Preferably, in step S3,
[0037] The density of the prepared silver nanogel is 10–30 mg / cm³. 3 .
[0038] Preferably, step S4 includes:
[0039] The nano-silver aerogel was pulverized and uniformly mixed with silicone oil, then an antioxidant was added. The mixture was then ball-milled to obtain the flexible, stretchable nano-silver aerogel conductive slurry.
[0040] The ball milling speed is 100 r / min to 500 r / min, and the time is 2 h to 8 h.
[0041] Preferably, in step S4,
[0042] The mass ratio of the nano-silver aerogel to the silicone oil is 1:(1-5);
[0043] The particle size of the pulverized silver nanogel is 1μm to 20μm.
[0044] The viscosity of the silicone oil is 100cp to 1000cp.
[0045] Preferably, in step S4,
[0046] The antioxidant is selected from one of the following: propyl gallate, 2,6-di-tert-butyl-4-methylphenol, tert-butylhydroquinone, vitamin C, vitamin E, sodium sulfite, or sodium metabisulfite.
[0047] The antioxidant accounts for 0.05% to 0.5% of the total mass of the flexible, stretchable nano-silver aerogel conductive paste.
[0048] The flexible stretchable nano-silver aerogel conductive paste according to the second aspect of the present invention is prepared by the preparation method of the flexible stretchable nano-silver aerogel conductive paste of any of the first aspects described above.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects:
[0050] The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to embodiments of the present invention uses a polymer scaffold as a flexible substrate to provide support and deformation capability. A thiol end-capping agent precisely positions the nano-silver particles at the ends of the polymer chains, allowing for controllable changes in particle spacing during material stretching and maintaining the conductive pathway. Furthermore, the reaction between the thiol end-capping agent and the polymer enables the disulfide bonds (SS) between the polymer chains to synergize with the silver-sulfur (Ag-S) coordination bonds, achieving self-healing during stretching of the material.
[0051] Furthermore, the method in the embodiments of the invention also provides a multi-level porous structure by directionally freezing the thiol-terminated prepolymer solution, thereby ensuring the high conductivity of the material, endowing the material with excellent flexibility and bending resistance, and adapting it to complex application scenarios.
[0052] The above and other objects, advantages and features of the present invention will become more apparent to those skilled in the art from the following detailed description of specific embodiments of the invention in conjunction with the accompanying drawings. Attached Figure Description
[0053] The following sections will describe some specific embodiments of the invention in detail by way of example and not limitation, with reference to the accompanying drawings. The same reference numerals in the drawings denote the same or similar parts or portions. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings:
[0054] Figure 1 This is a flowchart of a method for preparing flexible and stretchable nano-silver aerogel conductive paste according to an embodiment of the present invention. Detailed Implementation
[0055] In the description of this embodiment, it should be understood that the terms "length", "width", "height", "up", "down", "left", "right", "vertical", "horizontal", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the present invention.
[0056] As a specific embodiment of the present invention, refer to Figure 1 As shown, the preparation method of the flexible and stretchable nano-silver aerogel conductive paste according to the first aspect of the present invention may include the following steps:
[0057] S1, prepare a thiol-terminated prepolymer solution.
[0058] Specifically, the thiol-terminated prepolymer solution introduces disulfide bonds (SS) between the polymer chains, forming a dynamic bonding network that allows the material to reversibly break and recombine during stretching, adapting to material deformation. Furthermore, the dynamic properties of the disulfide bonds endow the material with self-healing capabilities while maintaining the stability of the conductive circuit.
[0059] S2, a silver ion solution and a reducing agent are added to the thiol-terminated prepolymer solution to reduce it and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints. Preferably, the TEM number-average particle size of the silver nanoparticles is 5–20 nm, and the particle size distribution index is 0–0.3.
[0060] Specifically, the thiol-terminated prepolymer solution introduces thiol groups (-SH) between the polymer chain endpoints, allowing the silver nanoparticles (Ag) in the silver ion solution to bind with the thiol groups through coordination bonds (Ag-S), forming a dynamic bonding network and enhancing the silver-polymer interface bonding. The coordination bonds (Ag-S) precisely anchor the silver nanoparticles to the polymer chain endpoints, ensuring uniform dispersion and stability of the conductive filler. Furthermore, during stretching, the silver nanoparticles can slide and reconstruct the conductive pathways through the coordination bonds, enhancing the continuity of the conductive pathways and maintaining the material's conductivity.
[0061] S3, a crosslinking agent is added to the colloidal solution and the solution is directionally frozen to form a gel. The gel is then immersed in a displacement agent to replace the gel, thus obtaining a nano-silver aerogel.
[0062] Specifically, a cross-linking agent is added to the colloidal solution to form a three-dimensional network through chemical cross-linking, and the three-dimensional network structure is further optimized through dynamic bonding networks (such as disulfide bonds and coordination bonds). The formation of a gel after directional freezing further enhances the orderliness of the three-dimensional network. Finally, the gel is immersed in a displacement agent, and the displacement preserves the three-dimensional network structure (i.e., silver nanogel). Preferably, the density of the prepared silver nanogel is 10–30 mg / cm³. 3 The resulting ultralight porous nanosilver aerogel has the characteristics of high specific area and low density.
[0063] S4. The nano-silver aerogel is pulverized and uniformly mixed with silicone oil to prepare a flexible and stretchable nano-silver aerogel conductive slurry.
[0064] In other words, the preparation method of the flexible and stretchable nano-silver aerogel conductive slurry of this invention constructs a polymer scaffold using a prepolymer and precisely anchors the nano-silver particles to the ends of the polymer chains using chemical methods (such as in-situ reduction), thereby ensuring controllable changes in particle spacing during material stretching and maintaining the continuity of the conductive circuit. Furthermore, the polymer scaffold is further optimized by the dynamic bonding network formed by disulfide bonds and coordination bonds introduced by the thiol end-capping agent, achieving reversible breakage / reconstruction of the conductive pathway during material stretching. In other words, the preparation method of the flexible and stretchable nano-silver aerogel conductive slurry of this application can achieve reversible breakage / reconstruction of the conductive pathway during material stretching, thereby providing an efficient conductive path and ensuring high conductivity and conductive stability of the material. In addition, the preparation method of the flexible and stretchable nano-silver aerogel conductive slurry of this application can endow the material with excellent flexibility and bending resistance, making it adaptable to complex application scenarios.
[0065] In some embodiments, step S1 may include:
[0066] A polymer prepolymer and a thiol-terminated agent are added to a solution and stirred until homogeneous to obtain a thiol-terminated prepolymer solution.
[0067] The molar ratio of the polymer prepolymer to the thiol end-capping agent is 1:(0.1~5). During stirring, the ambient temperature is 40℃~80℃, the stirring speed is 200r / min~500r / min, and the stirring time is 1.5h~3h.
[0068] Specifically, a polymer prepolymer and a thiol end-capping agent are mixed in a solution. The reaction between the polymer prepolymer and the thiol end-capping agent introduces disulfide bonds (SS) between the polymer chains formed by the prepolymer. These disulfide bonds (SS) enable reversible breakage and recombination during the stretching process, enhancing the material's flexibility and adaptability to various deformations. Furthermore, the dynamic properties of the disulfide bonds (SS) impart self-healing capabilities to the material, maintaining the stability of its conductive pathways. The molar ratio of the polymer prepolymer to the thiol end-capping agent is 1:(0.1–5), effectively ensuring the dynamic bond density and guaranteeing that the resistance fluctuation after cyclic stretching is less than or equal to 10%.
[0069] More specifically, when the molar ratio of polymer prepolymer to thiol end-capping agent is greater than 1:0.1, the dynamic bond density is insufficient, resulting in resistance fluctuations >10% after cyclic stretching; while when the molar ratio is less than 1:5, excessive crosslinking causes the elongation at break to decrease to <50%. More preferably, when the molar ratio is 1:(0.3~1), the material simultaneously satisfies the requirement of electrical conductivity >5×10⁻⁶. 4 S / m and elongation > 200%.
[0070] Among these factors, a low molar ratio of polymer prepolymer to thiol end-capping agent (1:(0.1-1)) is suitable for spray coating processes (low viscosity requirements); a high molar ratio (1:(1-5)) is suitable for 3D printing (high mechanical strength requirements). However, given the relatively high price of thiol end-capping agents, a ratio of 1:(0.3-1) is the most economical under cost control conditions.
[0071] Preferably, in step S1,
[0072] The polymer prepolymer is selected from one of polyurethane, polydimethylsiloxane, or polyacrylic acid;
[0073] The thiol end-capping agent is selected from one of 1,4-butanedithiol, 1,6-hexanedithiol, dithiodipropionic acid, mercaptopolyethylene glycol, 3-mercaptopropyltrimethoxysilane, cysteine, pentaerythritol tetra, trimethylolpropane, 1-octylthiol, mercaptoacetic acid, or mercaptoethanol.
[0074] The solution is selected from one of tetrahydrofuran, toluene, N,N-dimethylformamide, acetone, N-methylpyrrolidone, propylene glycol methyl ether acetate, or supercritical carbon dioxide.
[0075] In some embodiments, step S2 may include:
[0076] A silver ion solution and a reducing agent are added to a thiol-terminated prepolymer solution, and the mixture is ultrasonically dispersed at an ultrasonic frequency of 20 kHz to 60 kHz for 15 min to 60 min. Then, the mixture is reacted at an ambient temperature of 40 ℃ to 80 ℃ for 0.5 h to 3 h to reduce and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints.
[0077] Specifically, thiol end-capping agents are used to introduce thiol groups (-SH) between the polymer chain endpoints, which can form coordination bonds (Ag-S) with subsequently added silver nanoparticles. The thiol groups (-SH) precisely anchor the silver nanoparticles to the polymer chain endpoints, ensuring uniform dispersion of the conductive filler. Furthermore, the silver nanoparticles can slide and reconstruct conductive pathways through coordination bonds, thereby maintaining conductivity. However, ultrasonic dispersion times below 15 minutes may lead to insufficient reduction, while times exceeding 60 minutes can easily cause particle agglomeration.
[0078] Preferably, in step S2, the molar ratio of silver ions to reducing agent in the silver ion solution is 1:(1-8).
[0079] Specifically, a ratio less than 1:1 leads to incomplete reduction, causing Ag to... + Residues accelerate the oxidation of nano-silver (FTIR detected at 1720 cm⁻¹). -1 Carbonyl peak), when the ratio is greater than 1:8, it leads to supersaturated nucleation and the formation of ultrafine particles (<5nm). The excessively large specific surface area leads to an increased oxidation rate (TGA shows that the weight increases at 50℃).
[0080] Preferably, in step S2,
[0081] The silver ion solution is selected from one of silver nitrate, silver acetate, silver fluoroborate, or silver lactate, and the concentration of silver ions in the silver ion solution is 0.01 mol / L to 0.2 mol / L.
[0082] Specifically, when [Ag] + When the concentration is <0.01 mol / L, insufficient nucleation occurs, meaning the number of silver nanoparticles per unit volume is too low (<10). 5 Particles / μL) cause discontinuities in the conductive network (conductivity < 1 × 10⁻⁶). 3 S / m); In addition, it leads to low anchoring efficiency, that is, excessive thiol-terminated prepolymer, and unbound -SH groups initiate side reactions (such as disulfide crosslinking). This lower limit is set for the control of silver nanonucleation. And when [Ag + At concentrations >0.2 mol / L, Ostwald ripening occurs, meaning that at high concentrations, small particles dissolve and large particles grow (particle size >50 nm). Additionally, steric hindrance occurs, meaning the prepolymer endpoints are insufficient to completely anchor the silver nanoparticles, leading to agglomeration (PDI >0.5). This upper limit is set to control the balance between particle size and dispersibility.
[0083] Preferably, in step S2, the reducing agent is selected from ascorbic acid, sodium borohydride, sodium citrate, or glucose.
[0084] In some embodiments, step S3 may include:
[0085] A cross-linking agent is added to the colloidal solution, which is then injected into a mold and placed in an environment of -50℃ to -10℃ for 3 to 10 hours to induce ice crystal growth and form a hierarchical porous structure with oriented channels, thus forming a gel.
[0086] The orientation channels include primary channels and secondary channels. The primary channels are formed by ice crystals growing along a temperature gradient, with a pore size of 10–50 μm and an aspect ratio greater than 5. The secondary channels are formed by the aggregation of silver nanoparticles in the gaps between ice crystals, with a pore size of 100–500 nm. The volume ratio of the primary channels to the secondary channels is 1:(0.5–2).
[0087] The gel was immersed in a displacement agent to displace water, and then dried in a supercritical CO2 environment to obtain nano-silver aerogel.
[0088] The volume ratio of gel to the displacement agent is 1:(3-10), and the displacement time is 2h-24h.
[0089] The drying environment temperature is 32℃~50℃, the air pressure is 7.5Mpa~20Mpa, and the duration is 6h~24h.
[0090] Specifically, a cross-linking agent is added to the prepared colloidal solution to form a three-dimensional network through chemical cross-linking, and the dynamic bonding network formed by disulfide bonds (SS) and coordination bonds (Ag-S) can further optimize the three-dimensional network structure. The cross-linked colloidal solution is injected into a mold, and a hierarchical porous structure is formed by directional freezing. During the freezing process, ice crystal growth induces polymer chain alignment, which can further enhance the orderliness of the three-dimensional network.
[0091] It should be noted that the induced ice crystal growth to form oriented channels includes primary channels, which are large-sized channels formed by ice crystal growth through directional freezing technology. These channels have a diameter of 10μm to 50μm and an aspect ratio greater than 5 (extending along the temperature gradient direction). They are used to provide the material with high flexibility and compressibility to adapt to complex deformations. The induced ice crystal growth to form oriented channels also includes secondary channels, which are small-sized channels formed through the gaps between clusters of silver nanoparticles, exhibiting a honeycomb-like interconnected structure with a diameter of 100nm.
[0092] ~500nm, it is used to provide an efficient conductive path and enhance the conductivity of the material. The silver nanoparticles are mainly distributed on the walls of secondary pores, and their particle size distribution D 90≤25nm (measured by TEM analysis of 200 particles).
[0093] In some embodiments, step S4 may include:
[0094] Nano-silver aerogel was pulverized and uniformly mixed with silicone oil, then an antioxidant was added. After ball milling, a flexible and stretchable nano-silver aerogel conductive paste was obtained.
[0095] The ball milling speed is 100 r / min to 500 r / min, and the time is 2 h to 8 h.
[0096] Preferably, in step S4,
[0097] The mass ratio of the nano-silver aerogel to the silicone oil is 1:(1-5);
[0098] The particle size of the pulverized silver nanogel ranges from 1 μm to 20 μm.
[0099] The viscosity of silicone oil is 100cp to 1000cp.
[0100] Preferably, in step S4,
[0101] The antioxidant is selected from one of the following: propyl gallate, 2,6-di-tert-butyl-4-methylphenol, tert-butylhydroquinone, vitamin C, vitamin E, sodium sulfite, or sodium metabisulfite.
[0102] The antioxidant accounts for 0.05% to 0.5% of the total mass of the flexible, stretchable nano-silver aerogel conductive paste.
[0103] The flexible stretchable nano-silver aerogel conductive paste according to the second aspect of the present invention is prepared by the preparation method of the flexible stretchable nano-silver aerogel conductive paste of any of the first aspects described above.
[0104] The following specific embodiments further illustrate the flexible and stretchable nano-silver aerogel conductive slurry of this application and its preparation method.
[0105] Example 1:
[0106] Preparation of silver nano-aerogels
[0107] Step 1: Synthesis of polymer prepolymers
[0108] Polyurethane prepolymer and 1,4-butanedithiol were mixed in tetrahydrofuran at a molar ratio of 1:0.3 and stirred at 300 r / min for 2 h at 60 °C (while stirring, the tetrahydrofuran was heated to 60 °C, and then the polyurethane prepolymer and 1,4-butanedithiol were added, and stirring was continued for 2 h) to form a thiol-terminated polyurethane prepolymer solution.
[0109] Step 2: In-situ reduction of nano-silver
[0110] Add 0.1 mol / L silver nitrate and ascorbic acid (reducing agent, Ag) to the above solution. + The mixture was ultrasonically dispersed at a frequency of 40 kHz for 30 min with C6H8O6 in a molar ratio of 1:2, and then reacted at 60 °C for 1 h to generate PU-terminated silver nanoparticles (particle size of 15 nm).
[0111] Step 3: Sol-gel and directional freezing
[0112] Add 0.5% (w / w) of triethylenetetramine, a crosslinking agent, into a mold, place it on a copper plate at -30°C, and directionally freeze for 6 hours to induce ice crystal growth and form oriented channels.
[0113] Step 4: Supercritical drying
[0114] The gel was immersed in ethanol to displace the water, then dried in a supercritical CO2 drying autoclave, and then treated at 40℃ and 10MPa for 12 h to obtain a density of 15 mg / cm³. 3 Nano-silver aerogel.
[0115] Preparation of conductive paste
[0116] Step 1: Slurry preparation
[0117] The nano-silver aerogel was pulverized to a particle size of <10μm and mixed with silicone oil with a viscosity of 500cP at a mass ratio of 1:3. 0.1wt% of propyl gallate was added, and the mixture was ball-milled at 200r / min for 4h to form a uniform slurry, thus obtaining a flexible and stretchable nano-silver aerogel conductive slurry.
[0118] Step 2: Coating and Curing
[0119] The paste was screen-printed onto a 100μm thick silicone substrate, pre-cured at 80℃ for 1 hour, and then cured again at 120℃ for 2 hours to form a stretchable conductive film. The performance of the conductive film was then tested.
[0120] The specific tests were as follows: the initial conductivity was tested using the four-probe method; the sample was stretched to 200% and the resistance change was tested using a multimeter; the sample was subjected to 1000 cycles of stretching using a tensile testing machine, and the resistance after each stretch was recorded and the resistance fluctuation was calculated; the sample was bent to a bending radius of 0.5 mm and the resistance change was tested using a multimeter.
[0121] Example 2:
[0122] 1. Preparation of silver nanogels
[0123] Step 1: Synthesis of polymer prepolymers
[0124] Polydimethylsiloxane prepolymer (PDMS prepolymer, hydroxyl content 8%) and 1,4-butanedithiol were dissolved in toluene at a molar ratio of 1:0.4 and stirred at 350 r / min for 3 h at 70 °C to form a thiol-terminated PDMS solution.
[0125] Step 2: In-situ reduction of nano-silver
[0126] Add silver nitrate (AgNO3) and sodium borohydride (reducing agent) at a concentration of 0.15 mol / L to the above solution. + The molar ratio of AgNO3 to NaBH4 is 1:3. Silver nitrate (AgNO3) and sodium borohydride (as a reducing agent) at a concentration of 0.15 mol / L are added to the above solution. + Sodium borohydride powder was added in three portions (5 min apart) at a molar ratio of 1:3 with NaBH4. The mixture was ultrasonically dispersed at a frequency of 40 kHz for 30 min, and then reacted at 60 °C for 1 h (stirring speed 300 rpm). The reaction solution was centrifuged (8000 rpm, 10 min) to remove free Ag. + PDMS-terminated silver nanoparticles (15 nm in diameter) were generated.
[0127] Step 3: Sol-gel and directional freezing
[0128] Add 0.8% by mass of the crosslinking agent tetraethoxysilane, inject into a mold, and place on a copper plate at -40℃ for directional freezing for 8 hours to form a multi-level porous structure.
[0129] Step 4: Supercritical drying
[0130] The gel was immersed in acetone to replace the solvent, and then subjected to supercritical CO2 drying at 45℃ and 12MPa for 15h to obtain a density of 12mg / cm³. 3 Nano-silver aerogel.
[0131] 2. Preparation of Flexible Conductive Paste
[0132] Step 1: Slurry preparation
[0133] The aerogel was pulverized to a particle size of <8μm and mixed with silicone oil with a viscosity of 300cP at a mass ratio of 1:4. 0.2% propyl gallate was added, and the mixture was ball-milled at 220r / min for 5h to form a uniform slurry, thus obtaining a flexible and stretchable nano-silver aerogel conductive slurry.
[0134] Step 2: Coating and Curing
[0135] The slurry was sprayed onto a polyimide film with a thickness of 80 μm, pre-cured at 90°C for 1.5 h, and then cured again at 150°C for 3 h to form a stretchable conductive film. The performance of the conductive film was then tested (same as in Example 1).
[0136] Example 3
[0137] Preparation of silver nano-aerogels
[0138] Step 1: Synthesis of polymer prepolymers
[0139] Polyacrylic acid prepolymer (PAA, carboxyl content 10%) and 1,4-butanedithiol were dissolved in N,N-dimethylformamide (DMF) at a molar ratio of 1:0.2 and stirred at 280 r / min for 2.5 h at 50 °C to form a thiol-terminated PAA solution.
[0140] Step 2: In-situ reduction of nano-silver
[0141] Add silver nitrate (AgNO3) and sodium citrate (reducing agent) at a concentration of 0.08 mol / L, with a molar ratio of Ag... + The mixture of C6H5Na3O7 and 2.5 was ultrasonically dispersed at a frequency of 38 kHz for 35 min, and then reacted at 55 °C for 2 h to generate PAA-terminated silver nanoparticles (8 nm in diameter).
[0142] Step 3: Sol-gel and directional freezing
[0143] Add 0.3% (w / w) of crosslinking agent ethylenediamine, inject into a mold, and place on a copper plate at -25°C for directional freezing for 5 hours to form a gradient pore structure.
[0144] Step 4: Supercritical drying
[0145] The gel was immersed in isopropanol for displacement, and then subjected to supercritical CO2 drying at 35°C and 8 MPa for 10 h to obtain a density of 18 mg / cm³. 3 Aerogel.
[0146] Preparation of flexible conductive paste
[0147] Step 1: Slurry preparation
[0148] The aerogel was pulverized to a particle size of <5μm and mixed with fluorinated silicone oil with a viscosity of 200cP at a mass ratio of 1:2. 0.0% propyl gallate was added, and the mixture was ball-milled at 180r / min for 3h to form a uniform slurry, thus obtaining a flexible and stretchable nano-silver aerogel conductive slurry.
[0149] Step 2: Coating and Curing
[0150] The slurry was coated onto a 50 μm thick polyethylene terephthalate (PET) substrate by a scraping method, pre-cured at 70°C for 0.5 h, and then cured again at 100°C for 1.5 h to form a stretchable conductive film. The performance of the conductive film was tested (same as in Example 1).
[0151] Example 4
[0152] Preparation of silver nano-aerogels
[0153] Step 1: Synthesis of polymer prepolymers
[0154] Polyurethane prepolymer (PU, NCO content 8%) and 1,4-butanedithiol were dissolved in acetone at a molar ratio of 1:0.5 and stirred at 320 r / min for 3 h at 65 °C to form a thiol-terminated PU solution.
[0155] Step 2: In-situ reduction of nano-silver
[0156] Add silver nitrate (AgNO3) at a concentration of 0.2 mol / L and glucose (reducing agent) in a molar ratio of Ag... + :C6H 12 O6 was mixed at a ratio of 1:4 and ultrasonically dispersed at a frequency of 50 kHz for 50 min. Then, it was reacted at 75 °C for 1 h to generate PU-terminated silver nanoparticles (particle size 20 nm).
[0157] Step 3: Sol-gel and directional freezing
[0158] Add 1.0% by mass of hexamethylene diisocyanate, a crosslinking agent, inject into a mold, and freeze on a copper plate at -50°C for 10 hours to form honeycomb-like channels.
[0159] Step 4: Supercritical drying
[0160] The gel was immersed in an ethanol / water mixture for displacement, and then subjected to supercritical CO2 drying at 50℃ and 15MPa for 20 h to obtain a density of 10 mg / cm³. 3 Aerogel.
[0161] Preparation of flexible conductive paste
[0162] Step 1: Slurry preparation
[0163] The aerogel was pulverized to a particle size of <15μm and mixed with polyether-modified silicone oil with a viscosity of 800cP at a mass ratio of 1:5. 0.3wt% propyl gallate was added, and the mixture was ball-milled at a speed of 250r / min for 6h to form a uniform slurry, thus obtaining a flexible and stretchable nano-silver aerogel conductive slurry.
[0164] Step 2: Coating and Curing
[0165] The slurry was transferred onto a thermoplastic polyurethane elastomer (TPU) substrate with a thickness of 200 μm, pre-cured at 100°C for 2 h, and then cured again at 180°C for 4 h to form a stretchable conductive film. The performance of the conductive film was tested (same as in Example 1).
[0166] Example 5
[0167] Preparation of silver nano-aerogels
[0168] Step 1: Synthesis of polymer prepolymers
[0169] Polydimethylsiloxane prepolymer (NMP) and 1,4-butanedithiol were dissolved in N-methylpyrrolidone at a molar ratio of 1:1 and stirred at 350 r / min for 2.5 h at 70 °C to form a thiol-terminated NMP solution.
[0170] Step 2: In-situ reduction of nano-silver
[0171] Add silver nitrate (AgNO3) at a concentration of 0.2 mol / L and glucose (reducing agent) in a molar ratio of Ag... + :C6H 12 O6 was mixed at a ratio of 1:8 and ultrasonically dispersed at a frequency of 55 kHz for 60 min. Then, it was reacted at 80 °C for 1.5 h to generate NMP-terminated silver nanoparticles (particle size 25 nm).
[0172] Step 3: Sol-gel and directional freezing
[0173] Add 1.0% by mass of hexamethylene diisocyanate as a crosslinking agent, inject into a mold, and freeze on a copper plate at -50°C for 9 hours to form honeycomb-like channels.
[0174] Step 4: Supercritical drying
[0175] The gel was immersed in an ethanol / water mixture for displacement, and then subjected to supercritical CO2 drying at 45℃ and 18MPa for 22 h to obtain a density of 25 mg / cm³. 3 Aerogel.
[0176] Preparation of flexible conductive paste
[0177] Step 1: Slurry preparation
[0178] The aerogel was pulverized to a particle size of <10μm and mixed with polyether-modified silicone oil with a viscosity of 900cP at a mass ratio of 1:5. 0.4wt% propyl gallate was added, and the mixture was ball-milled at 300r / min for 7h to form a uniform slurry, thus obtaining a flexible and stretchable nano-silver aerogel conductive slurry.
[0179] Step 2: Coating and Curing
[0180] The slurry was transferred onto a silicone substrate with a thickness of 100 μm, pre-cured at 90°C for 1.8 h, and then cured again at 180°C for 2 h to form a stretchable conductive film. The performance of the conductive film was then tested (same as in Example 1).
[0181] Comparative Example 1
[0182] Preparation of silver nano-aerogels
[0183] Step 1: Synthesis of polymer prepolymers
[0184] Same as in Example 1, but without adding 1,4-butanedithiol, only PU prepolymer was mixed with THF, and other conditions remained unchanged.
[0185] Step 2: In-situ reduction of nano-silver
[0186] Same as Example 1, but observation by transmission electron microscopy (TEM) revealed that the silver nanoparticles were not anchored to the ends of the polymer chains and were in a random dispersed state.
[0187] Steps 3-4: Same as in Example 1.
[0188] Preparation of flexible conductive paste
[0189] Same as Example 1.
[0190] The test conditions were the same as in Example 1.
[0191] Comparative Example 2
[0192] Preparation of silver nano-aerogels
[0193] Steps 1-4: Same as in Example 1, but without the addition of propyl gallate.
[0194] Preparation of flexible conductive paste
[0195] Same as Example 1.
[0196] The test conditions were the same as in Example 1.
[0197] Comparative Example 3
[0198] Preparation of silver nano-aerogels
[0199] Steps 1-2: Same as in Example 1, but without directional freezing, allowing the solution to gel naturally at room temperature.
[0200] Steps 3-4: Same as in Example 1.
[0201] Preparation of flexible conductive paste
[0202] Same as Example 1.
[0203] The test conditions were the same as in Example 1.
[0204] Table 1 shows the performance evaluation of the conductive films prepared from the conductive pastes of each embodiment and comparative example.
[0205]
[0206] Analysis of Table 1 shows that:
[0207] Example 1
[0208] Initial conductivity: 6.5 × 10 4 S / m; The high initial conductivity indicates that the silver nanoparticles formed a continuous conductive network in the aerogel, and the thiol end-capping agent enhanced the silver-polymer interface bonding.
[0209] Resistance change rate at 200% stretching: <3%; dynamic disulfide bonds (SS) and coordination bonds (Ag-S) are reversibly broken / recombined during stretching, realizing dynamic self-repair of the conductive path and ensuring resistance stability.
[0210] Resistance fluctuation after 1000 cycles of cyclic tensile testing: ±3%; the extremely low resistance fluctuation indicates that the material has excellent durability and dynamic self-healing ability under cyclic tensile testing.
[0211] Bending life: >400,000 times; the ultra-long bending life indicates that the multi-level porous structure of the aerogel and the flexible polymer scaffold endow the material with excellent bending resistance.
[0212] The rate of change in resistance after bending radius of 0.5 mm is 12%; the small rate of change in resistance indicates that the material can still maintain good conductivity under small bending radius.
[0213] In summary, Example 1 demonstrates excellent performance in terms of conductivity, tensile stability, cycle durability, and flexural strength, exhibiting the best overall performance.
[0214] Example 2
[0215] Initial conductivity: 1.2 × 10⁻⁶ 5 S / m; the higher initial conductivity indicates that the PDMS matrix and optimized silver nanoparticle content further improve the quality of the conductive network.
[0216] Resistance change rate at 200% stretching ratio: <4%; the resistance change rate is slightly higher than that of Example 1, but still significantly better than the prior art, indicating that the dynamic bonding network is still effective in the PDMS matrix.
[0217] Resistance fluctuation after 1000 cycles of cyclic stretching: ±7%; the resistance fluctuation is slightly higher than that in Example 1, which may be related to the lower elastic modulus of the PDMS matrix.
[0218] Bending life: >200,000 cycles; the long bending life indicates that the PDMS matrix has good flexibility and fatigue resistance.
[0219] The rate of change in resistance after bending radius of 0.5 mm was 18%. The rate of change in resistance was slightly higher than that in Example 1, but still at a low level, indicating that the material performs well under small bending radii.
[0220] In summary, Example 2 exhibits excellent conductivity and bending resistance, but its cycle durability is slightly lower than that of Example 1.
[0221] Example 3
[0222] Initial conductivity: 9×10 4 S / m; the high initial conductivity indicates that the PAA matrix and the silver nanoparticles form an effective conductive network.
[0223] Resistance change rate at 200% stretching: <5%; the resistance change rate is slightly higher than that of Examples 1 and 2, but still significantly better than the prior art, indicating that the dynamic bonding network is effective in the PAA matrix.
[0224] Resistance fluctuation after 1000 cycles of tensile testing: ±5%; the small resistance fluctuation indicates that the material has good durability under cyclic tensile testing.
[0225] Bending life: >250,000 cycles; the long bending life indicates that the PAA matrix has good bending resistance.
[0226] The rate of change in resistance after bending radius of 0.5 mm was 15%. The rate of change in resistance was slightly higher than that in Example 1, but still at a low level, indicating that the material performs well under small bending radii.
[0227] In summary, Example 3 demonstrates a good balance in conductivity, cycle durability, and bending resistance, exhibiting excellent overall performance.
[0228] Example 4
[0229] Initial conductivity: 1.5 × 10 5 S / m; the highest initial conductivity indicates that the optimized nano-silver content and polymer scaffold further improved the quality of the conductive network.
[0230] Resistance change rate at 200% stretching: <2%; the lowest resistance change rate indicates that the dynamic bonding network performs best at high nanosilver content.
[0231] Resistance fluctuation after 1000 cyclic stretching cycles: ±6%; the resistance fluctuation is slightly higher than in Example 1, which may be related to local stress concentration caused by high nano-silver content.
[0232] Bending life: >300,000 cycles; the long bending life indicates that the material still has good bending resistance even with high nano-silver content.
[0233] The rate of change in resistance after bending radius of 0.5 mm was 25%. The rate of change in resistance was slightly higher than that of other embodiments, but still within an acceptable range, indicating that the material performs well under small bending radii.
[0234] In summary, Example 4 showed the best performance in terms of conductivity and tensile stability, but its cycle durability and flexural strength were slightly lower than those of Example 1.
[0235] Example 5
[0236] Initial conductivity: 1.1 × 10⁻⁶ 5 Although the S / m remains at a high level, it is lower than that of Example 4, indicating that controlling the size of the silver nanoparticles is crucial for improving conductivity.
[0237] The rate of change in electrical resistance at 200% stretching is <4%. In Example 5, the molar ratio of the polymer prepolymer to the thiol end-capping agent is 1:1, which can form abundant disulfide bonds (SS) and coordination bonds (Ag-S). As shown in Examples 1-4, these dynamic bonds can be reversibly broken / reassembled during stretching, thereby effectively maintaining the stability of the conductive pathway.
[0238] Resistance fluctuation after 1000 cycles of stretching: ±9%. Due to the influence of particle size, the cycle durability is weaker than that of Example 1 (±3%), indicating that large-size silver nanoparticles have an adverse effect on the long-term cycle stability of the material.
[0239] Bending life: >200,000 cycles; this is mainly attributed to the aerogel hierarchical pore structure and flexible polymer scaffold in the material, which together provide the material with a certain degree of bending resistance.
[0240] The rate of change in resistance after bending radius of 0.5 mm was 25%; this is still lower than that of Example 1, indicating that large-diameter silver nanoparticles may reduce the bending resistance of the material.
[0241] In summary, compared with Examples 1-4, Example 5 has certain advantages in conductivity, but its cycle durability and bending resistance are inferior.
[0242] Comparative Example 1
[0243] Initial conductivity: 6×10 4 S / m; The low initial conductivity indicates that the lack of anchored silver nanoparticles led to a decrease in the quality of the conductive network.
[0244] Resistance change rate at 200% stretching: >25%; the significant increase in resistance change rate indicates that unanchored silver nanoparticles cannot maintain the stability of the conductive pathway during stretching.
[0245] Resistance fluctuation after 1000 cycles of stretching: ±25%; the significant increase in resistance fluctuation indicates that the unanchored silver nanoparticles cause the conductive network to gradually fail during cyclic stretching.
[0246] Bending life: <100,000 cycles; the shorter bending life indicates that the lack of anchored silver nanoparticles leads to a decrease in the material's bending resistance.
[0247] The rate of change in resistance after bending to a radius of 0.5 mm was 55%. The significant increase in the rate of change in resistance indicates that the lack of anchored silver nanoparticles severely disrupted the conductive pathways after bending.
[0248] In summary, the significant performance degradation in Comparative Example 1 demonstrates the crucial role of thiol-capped anchored silver nanoparticles in enhancing material properties.
[0249] Comparative Example 2
[0250] Initial conductivity: 1.1 × 10⁻⁶ 5 S / m; The high initial conductivity indicates that the absence of antioxidants has little impact on the initial conductivity.
[0251] Resistance change rate at 200% stretching: <4%; the low resistance change rate indicates that the dynamic bonding network remains effective even without the addition of antioxidants.
[0252] Resistance fluctuation after 1000 cycles of stretching: ±18%; the significant increase in resistance fluctuation indicates that the lack of added antioxidants led to the oxidation of silver particles and the gradual failure of the conductive network.
[0253] Bending life: <100,000 cycles; a shorter bending life indicates that the lack of antioxidants has led to a decrease in the material's bending resistance.
[0254] The resistance change rate after bending radius of 0.5 mm was 38%. The significant increase in resistance change rate indicates that the lack of added antioxidants exacerbated the damage to the conductive pathways after bending.
[0255] In conclusion, the performance degradation in Comparative Example 2 demonstrates the crucial role of antioxidants in improving the long-term stability and durability of materials.
[0256] Comparative Example 3
[0257] Initial conductivity: 4 × 10 4 S / m; the lowest initial conductivity indicates that the removal of directional freezing led to a significant decrease in the quality of the conductive network.
[0258] The resistance change rate at a stretching ratio of 200% is >30%; the significant increase in the resistance change rate indicates that the disordered pore structure makes the conductive pathways prone to breakage during stretching.
[0259] Resistance fluctuation after 1000 cycles of stretching: ±20%; the significant increase in resistance fluctuation indicates that the disordered pore structure causes the conductive network to gradually fail during cyclic stretching.
[0260] Bending life: <20,000 cycles; the extremely short bending life indicates that the disordered pore structure leads to a significant decrease in the material's bending resistance.
[0261] The resistance change rate after bending to a radius of 0.5 mm was 42%. The significant increase in the resistance change rate indicates that the disordered pore structure caused severe damage to the conductive path after bending.
[0262] In conclusion, the significant performance degradation in Comparative Example 3 demonstrates the crucial role of directional freezing technology in constructing multi-level porous structures and improving material properties.
[0263] Overall Conclusion
[0264] Examples 1-5: By optimizing the material composition and structural design, high conductivity, excellent tensile properties, cycle durability and bending resistance were achieved, with Examples 1 and 4 showing the best overall performance.
[0265] Comparative Examples 1-3: After removing key components or eliminating key processes, the material properties decreased significantly, demonstrating the crucial role of thiol end-capping agents, antioxidants, and directional freezing processes in improving material properties.
[0266] These results demonstrate that the conductive paste of this application has significant advantages in terms of high conductivity, dynamic self-healing ability and durability, and can be applied to demanding fields such as flexible electronics and wearable devices.
[0267] Therefore, those skilled in the art should recognize that although numerous exemplary embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Thus, the scope of the present invention should be understood and construed as covering all such other variations or modifications.
Claims
1. A method for preparing a flexible and stretchable nano-silver aerogel conductive paste, characterized in that, Includes the following steps: S1, prepare a thiol-terminated prepolymer solution; S2, add silver ion solution and reducing agent to the thiol-terminated prepolymer solution to reduce and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints, wherein the TEM number-average particle size of the silver nanoparticles is 5-20 nm and the particle size distribution index is 0-0.
3. S3, add a crosslinking agent to the colloidal solution and freeze it in a directional manner to form a gel, then immerse the gel in a displacement agent to displace it, thus obtaining a nano-silver aerogel; S4, the nano-silver aerogel is pulverized and uniformly mixed with silicone oil to obtain the flexible and stretchable nano-silver aerogel conductive slurry.
2. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 1, characterized in that, Step S1 includes: A polymeric prepolymer and a thiol-terminated agent are added to a solution and stirred until homogeneous to obtain the thiol-terminated prepolymer solution. The molar ratio of the polymer prepolymer to the thiol end-capping agent is 1:(0.1-5). During the stirring process, the ambient temperature is 40℃~80℃, the stirring speed is 200r / min~500r / min, and the stirring time is 1.5h~3h.
3. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 2, characterized in that, In step S1 The polymer prepolymer is selected from one of polyurethane, polydimethylsiloxane, or polyacrylic acid. The thiol end-capping agent is selected from one of 1,4-butanedithiol, 1,6-hexanedithiol, dithiodipropionic acid, mercaptopolyethylene glycol, 3-mercaptopropyltrimethoxysilane, cysteine, pentaerythritol tetramethylolpropane, 1-octylthiol, mercaptoacetic acid, or mercaptoethanol. The solution is selected from one of tetrahydrofuran, toluene, N,N-dimethylformamide, acetone, N-methylpyrrolidone, propylene glycol methyl ether acetate, or supercritical carbon dioxide.
4. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 1, characterized in that, Step S2 includes: A silver ion solution and a reducing agent are added to the thiol-terminated prepolymer solution, and the mixture is ultrasonically dispersed at an ultrasonic frequency of 20 kHz to 60 kHz for 15 min to 60 min. Then, the mixture is reacted at an ambient temperature of 40 ℃ to 80 ℃ for 0.5 h to 3 h to reduce and generate a colloidal solution of silver nanoparticles modified with prepolymer endpoints.
5. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 4, characterized in that, In step S2 The molar ratio of silver ions to reducing agent in the silver ion solution is 1:(1-8).
6. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 4, characterized in that, In step S2 The silver ion solution is selected from one of silver nitrate, silver acetate, silver fluoroborate or silver lactate, and the concentration of silver ions in the silver ion solution is 0.01 mol / L to 0.2 mol / L.
7. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 4, characterized in that, In step S2 The reducing agent is selected from one of ascorbic acid, sodium borohydride, sodium citrate, or glucose.
8. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 1, characterized in that, Step S3 includes: A crosslinking agent is added to the colloidal solution, which is then injected into a mold and placed in an environment of -50℃ to -10℃ for 3 to 10 hours to induce ice crystal growth and form oriented channels with a hierarchical porous structure, thus forming a gel. The oriented channels include primary channels and secondary channels. The primary channels are formed by ice crystals growing along a temperature gradient, with a pore size of 10-50 μm and an aspect ratio greater than 5. The secondary channels are formed by the aggregation of the silver nanoparticles in the gaps between the ice crystals, with a pore size of 100-500 nm. The volume ratio of the primary channels to the secondary channels is 1:(0.5-2). The gel was immersed in a displacement agent to displace water, and then dried in a supercritical CO2 environment to obtain the nano-silver aerogel. The volume ratio of the gel to the displacement agent is 1:(3-10), and the displacement time is 2h-24h. The drying environment is characterized by a temperature of 32℃ to 50℃, an air pressure of 7.5 MPa to 20 MPa, and a duration of 6 hours to 24 hours.
9. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 8, characterized in that, In step S3 The density of the prepared silver nanogel is 10–30 mg / cm³. 3 .
10. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 1, characterized in that, Step S4 includes: The nano-silver aerogel was pulverized and uniformly mixed with silicone oil, then an antioxidant was added. The mixture was then ball-milled to obtain the flexible, stretchable nano-silver aerogel conductive slurry. The ball milling speed is 100 r / min to 500 r / min, and the time is 2 h to 8 h.
11. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 10, characterized in that, In step S4 The mass ratio of the nano-silver aerogel to the silicone oil is 1:(1-5); The particle size of the pulverized silver nanogel is 1μm to 20μm. The viscosity of the silicone oil is 100cp to 1000cp.
12. The method for preparing the flexible and stretchable nano-silver aerogel conductive paste according to claim 10, characterized in that, In step S4 The antioxidant is selected from one of the following: propyl gallate, 2,6-di-tert-butyl-4-methylphenol, tert-butylhydroquinone, vitamin C, vitamin E, sodium sulfite, or sodium metabisulfite. The antioxidant accounts for 0.05% to 0.5% of the total mass of the flexible, stretchable nano-silver aerogel conductive paste.
13. A flexible and stretchable nano-silver aerogel conductive paste, characterized in that, The flexible and stretchable nano-silver aerogel conductive slurry is prepared by any one of the methods described in claims 1-12.
